2013
DOI: 10.1007/s00228-013-1560-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of information in the Summaries of Product Characteristics for dose adjustment in renal impairment

Abstract: Based on our analysis, current versions of SmPCs are characterised by several information deficits and by containing recommendations that are not relevant to clinical practice in terms of dose adjustment in renal impairment. These shortcomings might limit their usefulness for healthcare professionals and integration into clinical decision-making support systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
1
13
0
3
Order By: Relevance
“…Despite being considered a leading source of information for safety data and evidence-based prescribing decisions [15], SmPCs have been criticized for containing important clinical pharmacology information deficits [16], for being suboptimal sources of information for drug−drug interactions [17], food−drug interactions [18], therapeutic drug monitoring [19], or dose adjustment in renal impairment [20]. In addition, SmPCs have also been criticized for being too verbose, lacking standardization and being heterogeneous [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being considered a leading source of information for safety data and evidence-based prescribing decisions [15], SmPCs have been criticized for containing important clinical pharmacology information deficits [16], for being suboptimal sources of information for drug−drug interactions [17], food−drug interactions [18], therapeutic drug monitoring [19], or dose adjustment in renal impairment [20]. In addition, SmPCs have also been criticized for being too verbose, lacking standardization and being heterogeneous [21].…”
Section: Introductionmentioning
confidence: 99%
“…3 It might be relevant to recall that a similar issue as the one bs_bs_banner Letters to the Editor described by the authors was found in the official labelling in the European Union, the so-called Summaries of Product Characteristics (SmPC). 4 It might also be important to point out that discrepancies in renal drug dosing recommendations do have a primary origin that is related to the lack of uniformity in the definition of stages of renal impairment. Although the European Union regulation 3 and other international guidelines 5 clearly describe intervals to define each stage of renal impairment, these recommendations are not always followed.…”
Section: Lack Of Harmonisation In the Classification Of Renal Impairmmentioning
confidence: 99%
“…3 The same exclusion criteria applied in a previous study were considered for this analysis. 4 Out of the 309 (53.1%) SmPC that referred to a mild, moderate or severe stage of renal impairment, 200 (64.7%) presented explicit creatinine clearance limits to define these stages. Instead of complying with the European Union regulation, SmPC presented 11 different creatinine clearance ranges for mild renal impairment; 10 different ranges for mild to moderate renal impairment; 14 different ranges for moderate renal impairment; 3 different ranges for moderate to severe renal impairment; and 18 different creatinine clearance ranges for severe renal impairment.…”
Section: Lack Of Harmonisation In the Classification Of Renal Impairmmentioning
confidence: 99%
“…However, Salgado et al [7] analyzed and assessed the clinical relevance of the method of dose adjustment in patients with renal insufficiency for the medications that were approved by the European Medicines Agency (EMA) with the Summaries of Product Characteristics (SmPCs) in Europe, and they concluded that only 48.8% of them provided information that was both explicit and relevant [7].…”
Section: Introductionmentioning
confidence: 99%